Situation Report: Poland, 3 July 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Results of Tito's Visit to Poland Gomulka and the Chinese Question The 4th of July Reception in Warsaw Polish Press Comments on Robert Kennedy's Visit Poland on the Status of West Berlin Oder-Neisse Line More on Writers Protesting against Foreign Interference Liberalization of Polish-Swiss Trade